Costurando saberes e práticas de cuidado no climatério - Bisognin, Priscila (2016)
More than one phase in a woman's life, which can pass unnoticed by the health services, the menopause is a period of great significance that needs to be lived in its fullness. In this perspective, understanding the sociocultural context of each woman contributes to the nurses develop their practices based on increased understanding of the determinants of health-disease process. Thus, this study had as objective to know the knowledge and care practices in climacteric women linked to Family Health Strategy in a city from Bento Gonçalves, RS. This is a field research, descriptive with qualitative approach and intentional choice of eight participants for the study. Inclusion criteria: to ensure that all participants had psychocognitive able to participate in the data production process, we asked the doctor or nurse to indicate the possible participants also were included women living in the ESF coverage area that was the scene of this study in the ages between 40 and 65 years. And as exclusion criteria, women who underwent bilateral oophorectomy associated or not to hysterectomy. The data were produced only after approval of the project by the Research Ethics Committee of UFSM under CAAE 39318614.0.0000.5346. The main data production technique was the group interview in the context of cloth doll workshop and to characterize the group, individual semi-structured interview that occurred between February and March 2015, so that after the transcription process, the details were analyzed by the operative proposal of Minayo. The thematic groups were the followings: Women meeting of the climacteric: aspects and impressions; Aligning the seam: knowledge about the climacteric; Knowledge and health care practices during menopause: seams between the learned, and said the veiled and necessary care during menopause: plots between affection and religiosity. Developed health care practices cover from the popular practices, such as using showers, leisure activities, the practice of religion. The learned on perimenopause or menopause enhances the learning that occurs among women and generations, in which knowledge is constructed from mother to daughter, from grandmother to grand-daughter, among friends or in the workplace and in a punctual manner, observed The influence of some health professionals in the care developed by the participants. It aimed the need to increase the attention given to this female audience for parts of health professionals, especially nurses, as well as to reinforce the social support these women.